2014
DOI: 10.1016/j.carbpol.2013.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the molecular basis for the metal-mediated assembly of alginate gels

Abstract: 17The binding of sodium and calcium ions to single and multiple poly-G decamer strands has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…This result reflects our current understanding that the minimum length of a stable junction zone is 8 guluronic acids, capable of complexing 4 Ca 2+ ions (Stokke et al, 1993) and so we identify the strong interaction observed for the 4-site oligoG as the eggbox junction zone. Candidates for the identity of the weaker interaction may be the 'tilted eggbox', formed at low ratios of Ca 2+ to G in alginates (Borgogna, Skjåk-Braek, Paoletti, & Donati, 2013) or the perpendicular junction involving 3 Ca 2+ ions identified by Stewart et al (Stewart, Gray, Vasiljevic, & Orbell, 2014) from molecular dynamics simulations. The hypothesis that junction zones longer than 8 monomers take longer than 20 ms to form was tested for the 2-, 4-and 10-site oligoGs by increasing the dwell time of the AFM probe at the surface to from 0 to 50, 200 and 500 ms (giving total times that the probe and sample are within 20nm of each other of 20, 70, 220 and 520 ms).…”
Section: Distinguishing Single and Multiple Bond Rupture Eventsmentioning
confidence: 99%
“…This result reflects our current understanding that the minimum length of a stable junction zone is 8 guluronic acids, capable of complexing 4 Ca 2+ ions (Stokke et al, 1993) and so we identify the strong interaction observed for the 4-site oligoG as the eggbox junction zone. Candidates for the identity of the weaker interaction may be the 'tilted eggbox', formed at low ratios of Ca 2+ to G in alginates (Borgogna, Skjåk-Braek, Paoletti, & Donati, 2013) or the perpendicular junction involving 3 Ca 2+ ions identified by Stewart et al (Stewart, Gray, Vasiljevic, & Orbell, 2014) from molecular dynamics simulations. The hypothesis that junction zones longer than 8 monomers take longer than 20 ms to form was tested for the 2-, 4-and 10-site oligoGs by increasing the dwell time of the AFM probe at the surface to from 0 to 50, 200 and 500 ms (giving total times that the probe and sample are within 20nm of each other of 20, 70, 220 and 520 ms).…”
Section: Distinguishing Single and Multiple Bond Rupture Eventsmentioning
confidence: 99%
“…The use of sodium alginate (SA), a natural polymer extracted from brown seaweed, has found numerous applications . The reasons for this success are its biocompatibility, renewability, low cost, and the ability to create gel in the presence of bivalent ions . This property is directly correlated to its composition.…”
Section: Introductionmentioning
confidence: 99%
“…This polymer has shown interesting characteristics in many fields and applications, from pharmaceutical to environmental protection [2,3]. This wide range of applications is due to its ability to form a physical hydrogel, when bivalent cations (Me 21 ) are added to the alginate solution [4]. The polymer chain is made of (1,4)-linked b-D-mannuronic acid (M), and its C-5 epimere, a-Lguluronic acid (G), able to connect to each other in long sequences of M-Blocks, G-Blocks, and MG-Blocks [5,6].…”
Section: Introductionmentioning
confidence: 99%